Their Houses - Willis, Meredith Sue (Book collections on Project MUSE., 2018)
"As children, two sisters make homes for their toys out of matchboxes and shoeboxes, trying to create safe places after the loss of their mother to psychosis. Grace, a schoolteacher married to a doctor, appears to have a conventional life but has a breakdown during a move from one house to another. Dinah has married a self-ordained preacher and tries to keep her children safely separate from the world. Meanwhile, a childhood friend is linked to a militia's abortive attempt to blow up the FBI's fingerprint records facility in West Virginia, and later builds an isolated survivalist compound in the mountains. These three adults, closely bonded in childhood, are reunited on this acreage once owned by a white supremacist group, where they discover in various ways that there is no final protection, no matter how hard they strive to find it or make it"--